The Principle of Religious Moderation in Ibnu Arabi's Book Fushush Al Hikam - Mahmudi, Mahmudi (Proceedings of Annual Conference for Muslim Scholars, 2023)
This article argues that there are princples of religious moderation in Fushus al Hikam written by Ibnu ‘Arabi. The principle is about universal norm that become the core in life with the beginning. Fushus al hikam contents is about names of prophet that we find philosophy of life. The explanation in Fushus is not too long and not too short. This is the moderation of the writing. Ibnu ‘Arabi also explain with moderate explanation in each section. He started with explanation of Adam prophet and Idris. The method of this article is hermeneutic. The author uses subjective interpretation stated by Heidegger. The contribution of this article is to make our counsciosness aware that we have to live with moderate vision of Islam.